About G.R. Derzhavin’s poetic reflection on his creativity - Warda, Anna (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The article is devoted to the analysis of three poems by G. R. Derzhavin: My Idol (1794), Monument (1796) and The Offering to the Monarchine (1795) from the point of view of the reflection on artist’s work and fate after his death. In all these works, Derzhavin emphasizes the importance of Felitsa, his ode of 1782, and that his name would be known to other generations thanks to this work and its heroine, Felitsa, that is, Catherine II. It is also worth emphasizing that the poet looks at his work, his life, and posthumous fame from some perspective, although he is conscious of his talent and the level of his works.